HERPES ZOSTER IN RA PATIENT TREATED WITH METHOTREXATE - Yu. V. Muraviev; G. I. Gridneva (Безопасность и риск фармакотерапии, 2022)
This article describes herpes zoster (HZ) manifestation in RA patient treated with Methotrexate (MTX). The possibility of effective continuation of MTX after the symptoms of HZ resolve is demonstrated. The possibility of a causal relationship between the use of the MT and the manifestation HZ infection, and treatment options are discussed.